Chronic periodontitis as an etiology of sleep disturbances and premenstrual syndrome (PMS) - Haryono Utomo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
It is obvious that sleep disturbances may induced by acute pulpal or periodontal pain. Other causes of sleep disturbances which also termed as sleep dysfunction, or insomnia, according to the patient has to be treated by physician. Nevertheless, in a case report, surprisingly, periodontal treatment relieved sleep disturbances and premenstrual syndrome (PMS). Coincidentally, women also more vulnerable to sleep disturbances and periodontal disease. It is also interesting that the exact etiology of PMS is still unknown, and 80% women who suffered from PMS also experience sleep disturbances. Recently, there has been increasing numbers of literatures and evidence-based cases linking periodontal disease to systemic diseases. However, systemic effects of periodontal disease that lead to PMS which associated with sleep disturbances are rarely discussed. Several mechanisms had been proposed to involve in these symptoms: female sexual hormonal imbalance, stimulation of the hypothalamic-pituitary-adrenal axis (HPA-axis) and neurogenic switching mechanism. In addition, as estrogen makes women more susceptible to stress, it worsen the symptoms. The glucocorticoid hormones synthesized upon stimulation of the HPA-axis, either by stress or pro-inflammatory cytokines, may disrupt the sleep-wake cycle; and also create estrogen dominance. The aim of this study is to propose the etiopathogenesis of PMS which associated with sleep disturbances that may be related to chronic periodontitis. Since in this case report scaling and curettage resulted in the disappearing of PMS and sleep disturbances; the conclusion is that chronic periodontal disease may act as one of the etiologies of PMS and sleep disturbance.